REPRODUKSI ELIT PADA ERA OTONOMI DAERAH DI KABUPATEN BONE DAN GOWA - Arya Hadi Dharmawan (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2011)
This study aims to describe the response of ethnic political subculture Bugis Bone and Gowa Makassar in the reform era, especially in the formation of a new elite. The results of this study indicate that the model of ethnic identity politics in Bugis Bone strengthened and weakened in Gowa Makassar etnicity. Bone aristrocrat succes to maintain its relationship with the masses, rather Gowa aristocrat, was decreased political function. In Bone, there was an elite formation process that is conducted by the clan of Page, while the political stage in Gowa more open and filled by a diverse political community. Bone society’s political choices are more primordial, caused by power relations that continue to be maintained by the nobility of Bone. While the diversity of political choices made by people of Gowa due to the weak political control by elites and Gowa aristocrat.